DETERMINATION OF THE BODY COMPOSITION AS AN INDICATOR OF HUMAN HEALTH - Agajanyan, M.G.; Chshmarityan, M. V.; Sarkisyan, M. R. (Modern Psychology, 2019)
The doctrine of body composition has become an urgent area in the field of biology, medicine and valeology in the second half of the 20th century. The most common method of determination at present is bio-impedance analysis. Measuring weight alone does not give an accurate picture of the state of the body, since the body weight of a person is the sum of the weight of bones, muscles, adipose tissue, cerebrospinal fluid, etc. At the same time, two people with the same indicators of weight and height may differ in the level of content of adipose tissue, muscle mass, which significantly affects health and performance. A quantitative characteristic of body composition, an assessment of the ratio of all constituent components is a reflection of the energy balance, correlates with the physical performance of a person and reflects his adaptation to the changing environmental conditions of life. The most urgent problem is the study of body composition in sports, extreme conditions, morbid and premorbid conditions.
Keywords: body composition, body type, optimal weight, anthropometric indicators, physical performance